Embodied Learning in School Hygiene Education - Hiteshree; Supriya; Sheetal; Komal; Siddhi; Sneha Priya (The Bioscan, 2025)
Background: Personal hygiene plays a critical role in preventing communicable diseases and promoting physical, psychological, and academic well-being among school-aged children. In developing countries, inadequate hygiene practices remain a significant public health concern, particularly among primary school students. Conventional teaching methods often fail to bring sustained behavioural change, highlighting the need for interactive and child-centred educational strategies such as role play. Objective: To evaluate the effectiveness of role play on knowledge and practice regarding personal hygiene among primary school students in a selected government school of Gurugram, Haryana, and to examine the association between hygiene outcomes and selected socio-demographic variables. Methods: A quantitative, quasi-experimental one-group pre-test–post-test design was employed. The study included 60 primary school students studying in classes III–V, selected using a cluster random sampling technique. Data were collected using a validated structured questionnaire to assess knowledge and a Likert-scale-based observational checklist to assess hygiene practices. A structured role-play intervention focusing on key aspects of personal hygiene was administered. Pre-test and post-test scores were analysed using descriptive statistics and inferential tests, including paired t-test and chi-square test, with statistical significance set at p < 0.05. Results: The post-test findings demonstrated a statistically significant improvement in both knowledge and practice scores following the role-play intervention (p < 0.001). The mean knowledge score increased from 4.37 ± 0.80 to 7.02 ± 0.70, while the mean practice score improved from 3.93 ± 0.73 to 6.95 ± 0.84. A significant association was observed between hygiene outcomes and selected demographic variables, particularly socioeconomic status. Conclusion: Role play is an effective, engaging, and low-cost educational strategy for improving personal hygiene knowledge and practices among primary school children. Integrating role-play-based health education into school health programs may contribute to sustained behavioural change and improved child health outcomes. KEYWORDS Personal hygiene; Role play; Primary school children; Health education; Quasi-experimental study.